Enhancing User Comfort in Virtual Environments for Effective Stress Therapy: Design Considerations - Zaharuddin F.A.; Ibrahim N.; Yusof A.M. (Science and Information Organization, 2025)
Mental stress has emerged as a widespread concern in modern society, impacting individuals from diverse demographic backgrounds. Therefore, exploring effective methods for therapy, such as virtual environments tailored for stress management, is vital for advancing mental health and improving coping strategies. Prioritising user comfort in the design of virtual environments is essential for enhancing their efficacy in alleviating stress. By considering four design aspects of virtual environments that influence user comfort: (i) visual clarity, (ii) safety features, (iii) cognitive preparedness, and (iv) social support, this study intends to (i) evaluate the effectiveness of these four user-centered design elements in facilitating stress reduction and (ii) explore the underlying rationale behind their stress-reducing properties. This study utilised a mixed-methods approach comprising (i) experiments, (ii) questionnaires, and (iii) interviews. Following evaluation with the Depression Anxiety Stress Scale (DASS), 40 participants (10 men and 30 females) were chosen from the 55 healthy adults aged 20 to 60 who volunteered for the study. The findings validated the efficacy of all four design aspects in enhancing users? comfort during therapeutic sessions in virtual environments. This study offers important insights not only into the importance of user-centered design in creating virtual environments for stress management, where comfort markedly improves therapy outcomes but also contributes valuable knowledge to the fields of mental health and human-computer interaction, paving the way for further exploration of innovative therapeutic solutions for mental stress. ? (2024), (Science and Information Organization). All Rights Reserved.